Note—A Critical Note on a Result by Lemoine - Mitrani, I. (Management Science, 1979)
In a recent paper [Lemoine, A. J. 1977. Networks of queues—a survey of equilibrium analysis. Management Sci. 24 (4) 464–481.], A. J. Lemoine has derived an expression for the Laplace transform of the residence time T of a customer in a feed-forward exponential network. That expression was used to obtain the first two moments of T and the results agreed with those obtained earlier by Reich for the special case of single-server queues in tandem.